The development and happiness of very young children - Paul Anand; Laurence Roope (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The paper demonstrates how Sen's (1985) alternative approach to welfare economics can be used to shed light on the wellbeing of very young children. More specifically, we estimate versions of the three key relations from his framework using data from the German Socio-Economic Panel (SOEP, 2012) Survey. Our primary models provide evidence that skills are related to involvement in cognate activities with a parent, indicating a behavioural relationship between capabilities and activities which is not explicit in Sen's original set-up, but is key to the development and happiness of young children. A second set of models indicates that the daily activities of very young children are related to household income but that in some cases the association with parenting inputs is stronger. Thirdly, we report happiness regressions for the children which seem to suggest that shopping and reading are valued but that their distribution is limited in some cases - probably either by household income or parental education. Across the piece, we find that the number of siblings is negatively related to activity involvement with parents, as hypothesised by Becker, but positively related to everyday, motor and social skills. Combined with evidence from other studies, we conclude that the capability approach provides a useful framework for understanding the economics of wellbeing across the entire life course.
Keywords: D60; I31; J13; 330; child development; well-being; happiness; daily activities; capabilities